2022
DOI: 10.3390/ani12202845
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chiropractic Treatment on Limb Lameness and Concurrent Axial Skeleton Pain and Dysfunction in Horses

Abstract: Chiropractic care is a common treatment modality used in equine practice to manage back pain and stiffness but has limited evidence for treating lameness. The objective of this blinded, controlled clinical trial was to evaluate the effect of chiropractic treatment on chronic lameness and concurrent axial skeleton pain and dysfunction. Two groups of horses with multiple limb lameness (polo) or isolated hind limb lameness (Quarter Horses) were enrolled. Outcome measures included subjective and objective measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The lamest limb was determined to be the mode of the primary lameness limb amongst the three reviewers for each horse on each treatment day and was retained for statistical analysis. The median lameness score amongst reviewers for each limb was totalled to create a whole body lameness score out of 40 and was retained for statistical analysis 16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lamest limb was determined to be the mode of the primary lameness limb amongst the three reviewers for each horse on each treatment day and was retained for statistical analysis. The median lameness score amongst reviewers for each limb was totalled to create a whole body lameness score out of 40 and was retained for statistical analysis 16 …”
Section: Methodsmentioning
confidence: 99%
“…The median lameness score amongst reviewers for each limb was totalled to create a whole body lameness score out of 40 and was retained for statistical analysis. 16 Subjective 2.9 | Hepatic ultrasound and biopsy Hepatic ultrasound and biopsy were performed on day À1 and 22 as previously described. 11 A 5 MHz curvilinear ultrasound probe was utilised to identify hepatic parenchyma and the liver was examined for any evidence of hepatopathy.…”
Section: Pharmacokinetic Data Analysismentioning
confidence: 99%
“…In an attempt to evaluate its use in horses with lameness and concurrent axial skeleton pain and dysfunction, Maldonado et al showed some interesting, but somewhat inconsistent positive effects on lameness, back pain, and stiffness. 28 Limitations of their study included the presence of chronic, multilimb lameness and lack of pathoanatomical diagnoses. Further research into the benefits of chiropractic treatments in relation with back pain, lameness and motion asymmetry is still needed.…”
Section: Physiotherapy and Rehabilitation: Chiropractic Treatmentsmentioning
confidence: 99%